Management of low-grade malignant dermatofibrosarcoma protuberans without compromising oncologic clearance despite financial constraints - Vibhushit Kaul; Parvez David Haque; Nalini Calton; Sunil S Thomas (Wolters Kluwer Medknow Publications, 2018)
Dermatofibrosarcoma protuberans (DFSP) is a rare, locally aggressive soft-tissue tumor with high recurrence. Tissue biopsy, imaging, and staging form the diagnostic pathway, but sometimes investigations deter patients from low socioeconomic background. We present a case of malignant DFSP with adequate oncologic clearance despite financial constraints. A young male presented with a swelling over the right hip for 8 years. Although fine-needle aspiration, core biopsy, magnetic resonance imaging, and staging computerized axial tomography scan are the ideal management pathway, the patient refused these for an excision biopsy which would have sufficed if histology was benign. Histology reported a malignant fibrosarcomatous variant of DFSP. Wide excision of previous biopsy site and flap reconstruction was done as advised by the skin oncology multidisciplinary team (MDT) which confirmed oncologic clearance. We would ideally advocate a proper oncologic pathway, but in patients where finances restrict investigations oncologic clearance can still be achieved.